FORMATION OF LEGAL BASIS OF PUBLIC ADMINISTRATION IN THE CONTEXT OF DECENTRALIZATION OF POWER IN UKRAINE - Pavlyuk N.V. (Pressing Problems of Public Administration, 2017)
The basic regulations that contribute to the formation of the system of public administration in Ukraine, shows the interdependence of legal regulation of public administration and decentralization of power, the risks identi ed in the course of formation of legal framework of public administration, which includes changing the legal status of certain categories of jobs and their liability law unbalanced individual stages of decentralization of power to regional and local levels, the lack of proper legal regulation of political responsibility.